FENOMENA PEMELIHARAAN KUCING RAS DI NAGARI KUDU GANTING BARAT - Anisa Julita Fitri; Setiyo Utoyo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The phenomenon of breeding purebred cats in the village of Kudu Ganting Barat indicates a change in people's preferences towards pets. This study aims to understand the reasons why residents choose purebred cats over local cats, as well as the social impacts that arise. The research method used personal interviews with several villagers. The results of the study show that the maintenance of purebred cats is influenced by aesthetic factors, the cats' more obedient nature, as well as the habit of sharing among residents. In addition, this phenomenon strengthens social relationships in the village, although there are challenges in animal healthcare.